Pengembangan E-Module Berbasis Problem Based Learning Berbantuan Android Untuk Meningkatkan Kemampuan Komunikasi Matematis Peserta Didik SMP Kelas VIII - Dala Zulyani; Irwan Irwan; Yerizon Yerizon; Ali Asmar (JEMS: Jurnal Edukasi Matematika dan Sains, 2021)
This research is motivated by the low mathematical communication skills of junior high school students. This study aims to produce an Android-assisted problem-based learning E-module that is valid, practical, and effective to facilitate mathematical communication skills. This research is a development research carried out with the Plomp development model. The Plomp development model consists of three stages, namely preliminary investigation, prototyping stage, and assessment phase. The research was conducted at SMPN 3 Sungai Rumbai with the research subjects being material experts, linguists and educational technology experts as well as class VIII students at  SMPN 3 Sungai Rumbai. Data collection instruments in the form of interviews, documentation, questionnaires and test questions. The data obtained were analyzed using qualitative and quantitative data analysis techniques. The results showed that the problem-based learning-assisted mathematics E-module developed was classified as very valid (88.9% for lesson plans and 89.1% for e-module) and very practical, respectively 86.3% and 86, 5% (for small group lesson plans and e-modules) 85.9% and 85.5% (for large group lesson plans and e-modules). Meanwhile, based on the test results of the mathematical communication ability test, 76.2% of students met the criteria for the success of the mathematical communication ability test > 65%, meaning that the problem-based learning-assisted e-module was effective on mathematical communication skills.